2018
DOI: 10.3390/mi9100514
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance of Micro Hotplates with Novel Shapes Based on Single-Layer SiO2 Suspended Film

Abstract: In this paper, two kinds of suspended micro hotplate with novel shapes of multibeam structure and reticular structure are designed. These designs have a reliable mechanical strength, so they can be designed and fabricated on single-layer SiO2 suspended film through a simplified process. Single-layer suspended film helps to reduce power consumption. Based on the new film shapes, different resistance heaters with various widths and thicknesses are designed. Then, the temperature uniformity and power consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The RF power was continuously switched between 25 W and 60 W during the deep reactive ion etching of the Si wafer (etch rate 5.85 µm/min) with a chamber pressure of 4.5 Pa. The deep reactive ion etching was stopped on the etch stop layer, SiO 2 , beneath the membrane that was removed afterwards wet-chemically by oxide etch modified 7:1 of Honeywell, Germany because the incongruity of the internal stress due the presence of silicon oxide layer can hamper the stability of the membrane [4,16]. At the end, the chips were separated by sawing with a protective layer on the membrane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RF power was continuously switched between 25 W and 60 W during the deep reactive ion etching of the Si wafer (etch rate 5.85 µm/min) with a chamber pressure of 4.5 Pa. The deep reactive ion etching was stopped on the etch stop layer, SiO 2 , beneath the membrane that was removed afterwards wet-chemically by oxide etch modified 7:1 of Honeywell, Germany because the incongruity of the internal stress due the presence of silicon oxide layer can hamper the stability of the membrane [4,16]. At the end, the chips were separated by sawing with a protective layer on the membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The new technological advancement of micro fabrication has opened a platform for research and development to improve the performance and the characteristics of micro sensors for different applications such as combustible catalytic gas sensing [1,2,3]. A micro-machined thermal sensor with a stable membrane has become the focal point because of its small size and low power consumption [1,2,4,5,6]. Along with that, the sensors are expected to have perfect temperature homogeneity for the long-term stability of the catalyst, high thermal and mechanical strength to intensify the robustness in harsh environments, and compatibility with a standard microfabrication process [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the papers, [7,8], and [9], explore novel fabrication methodologies for MEMS devices. The remaining papers cover various novel MEMS sensors and actuators focusing on inertial micro-switch [10], micro hot plates [11], near IR spectrometry [12], magnetic microactuator [13], resonant microfluidic chip [14], high temperature pressure sensors [15], thermoelectric power sensors [16], and a review of the photonic crystal nanobeams for sensing [17].…”
mentioning
confidence: 99%
“…On the new device applications side, Peng et al presented an inertial microswitch with a very low threshold of 5 g and high threshold accuracy, leveraging squeeze film damping [10]. Liu et al presented novel designs of micro hot-plates with significantly improved temperature non-uniformity [11]. Huang et al reported on a novel MEMS-based infrared spectrometer operating in the range of 800–1800 nm with a wavelength resolution of 10 nm, which compared favorably with similar commercial systems [12].…”
mentioning
confidence: 99%